KENYAMANAN TERMAL DAN FAKTOR INDIVIDU YANG MEMPENGARUHI KEJADIAN HEAT STRAIN PADA PEKERJA LABELLING CANNING - Anisa Nur Fadhila; Indri Santiasih; Am Maisarah Disrinama (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
Heat Strain is a physiological response to heat loads where the body tries to dissipate heat to the environment to maintain a stable body temperature. The purpose of this study was to determine the effect of thermal comfort, physical workload, age, length of service, nutritional status, acclimatization status, health conditions, medication consumption and water consumption on heat strain events and provide recommendations. The sample used in this study of 36 workers. The analytical method used is ordinal logistic regression and heat strain event through the spread of the HSSI (Heat Strain Score Index) questionnaire. Ordinal logistic regression test results obtained that there are variables that affect the Heat Strain, namely the health condition p-value of 0.010 (α <0.05), consumption of drugs p-value 0.004 (α <0.05), and for consumption water p-value 0.023 (α <0.05). As for the variables of age, years of service, nutritional status have no relationship (p-value> 0.05). Recommendations made in the administrative control hierarchy are by adding mechanical ventilation in the form of blowers, rolling workers, socialization, adding gallon water and adjusting work clothes.